2017
DOI: 10.1038/cdd.2017.91
|View full text |Cite
|
Sign up to set email alerts
|

NOX2-dependent ATM kinase activation dictates pro-inflammatory macrophage phenotype and improves effectiveness to radiation therapy

Abstract: Although tumor-associated macrophages have been extensively studied in the control of response to radiotherapy, the molecular mechanisms involved in the ionizing radiation-mediated activation of macrophages remain elusive. Here we show that ionizing radiation induces the expression of interferon regulatory factor 5 (IRF5) promoting thus macrophage activation toward a pro-inflammatory phenotype. We reveal that the activation of the ataxia telangiectasia mutated (ATM) kinase is required for ionizing radiation-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 60 publications
6
55
0
Order By: Relevance
“…More recently, Ser486 in the so-called NOX-specific insertion sequence in the C-terminal NADPHbinding region was suggested to be an inhibitory phosphorylation site targeted by ataxia telangiectasia mutated kinase (ATM) (26). Since the NOX2 complex activates ATM (26,387), this might constitute a negative feedback loop to terminate the NOX2 activity. Interestingly, both ATM and PKC are expressed in skeletal muscle.…”
Section: Figmentioning
confidence: 99%
“…More recently, Ser486 in the so-called NOX-specific insertion sequence in the C-terminal NADPHbinding region was suggested to be an inhibitory phosphorylation site targeted by ataxia telangiectasia mutated kinase (ATM) (26). Since the NOX2 complex activates ATM (26,387), this might constitute a negative feedback loop to terminate the NOX2 activity. Interestingly, both ATM and PKC are expressed in skeletal muscle.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, a study demonstrated that NBN (Q9R207; S398, S605, S638, S644, S645), which was highly phosphorylated in our analysis, a subunit of MRN complex plays a role in macrophage functional activity. Moreover, several studies reported that ATM is involved in diverse macrophage function, inflammatory response, antimicrobial response, and protection against sepsis (11)(12)(13)(14)(15).…”
Section: Phosphoproteome Analysis Reveals a Regulatory Network Of M Ddrmentioning
confidence: 99%
“…Compelling evidence suggests the interplay and overlap between the DDR and innate immune responses: Some pathogens can induce genotoxic stress (8,9), while macrophages generate potent genotoxic species -ROS and NOS, during infections and tissue injury (10). Notably, the DDR has been reported to be involved in diverse macrophage functions such as inflammatory and antimicrobial responses and in the protection against sepsis (11)(12)(13)(14)(15). Specifically, ROS plays a role in differentiation of alternatively activated macrophages, while NOX2-induced ATM activation causes pro-inflammatory macrophage activation (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several in vitro studies underscore the direct effect of IR in macrophage activation. 1618 After in vitro cumulative ionizing radiation doses (2Gy/fraction/day), human monocyte-derived macrophages remain viable despite DNA damages, with an active metabolism. Cumulative doses of 10Gy increased proinflammatory, and decreased anti-inflammatory markers in macrophages.…”
Section: Macrophage Response To Radiotherapymentioning
confidence: 99%